TRIM16: a context-dependent E3 ligase in autophagy, oxidative stress, and immune regulation – from cancer and systemic disease - Dong, Hanchen; Jiang, Jiayu; Ni, Ke; Ren, Qinhong; Yang, Xinran; Shang, Liang; Cai, Baoshan; Li, Leping (Frontiers in Oncology, 2026)
TRIM16 is an atypical tripartite motif (TRIM) family E3 ligase that retains catalytic activity via its RING-like B-box domains, functioning primarily as a versatile molecular scaffold. This architecture enables TRIM16 to coordinate key cellular processes. These include oxidative stress responses (via the p62-KEAP1-NRF2 axis), secretory autophagy, lysophagy, and immune regulation, which collectively maintain cellular homeostasis. Emerging evidence highlights TRIM16 as a context-dependent regulator whose functions are shaped by cell type and microenvironment. In cancer, it acts as a tumor suppressor in most solid tumors by degrading oncoproteins and inducing cell cycle arrest, yet can paradoxically promote progression in pancreatic and hepatocellular carcinomas. Beyond oncology, TRIM16 protects against neurodegenerative, cardiovascular, and inflammatory diseases through quality control mechanisms. This review integrates recent advances to elucidate TRIM16’s molecular mechanisms and disease-specific functions, emphasizing its therapeutic and biomarker potential, and outlines future directions to decode its context-dependent actions for clinical translation.